PENGARUH KEBIJAKAN DECENTRALISASI FISKAL TERHADAP KAPASITAS KINERJA OTONOMI DAERAH DI WILAYAH KALIMANTAN - PKP2A III LAN, Tim (Pusjar SKPP Lembaga Administrasi Negara, 2008)
Fiscal decentralization that has been implemented since 2001 is logical implication of decentralization system (regional autonomy) in unitary state of Republic Indonesia in order to cost the authority given to local governments (money follows function). Fiscal Decentralization system is implemented to give a large discretion for local governments in managing their revenue and expenditure as one of stimuli to build the regional economics, but for about seven years implementation of fiscal decentralization, their dependency on fiscal transfer just decrease slightly. It is shown by the amount of balancing fund that still has the highest portion in local government revenue and expenditure. The result of the research shows that the average proportion of balancing fund for provinces in Kalimantan still achieves more than 60%, even the local governments (districts) has higher dependency on central government transfer. Considering this condition, reducing the central governments transfer in significant amount will disturb the local autonomy of performance capacity. Finally, it will threaten the regional development sustainability. Keywords: Fiscal decentralization, Decentralization system, Balancing fund, Performance capacity